Analysis of English Subject Education in Indonesia and South Korea: An Approach to Curriculum, Teaching Methods and Learning Outcomes - Zulhaidir, Zulhaidir; Susanti, L.R Retno; Yadi, Farhan; Hudaidah, Hudaidah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This study analyzes the comparison of English education systems in Indonesia and South Korea through a quantitative approach, focusing on three main aspects: curriculum, teaching methods, and learning outcomes. Data was collected through analysis of curriculum documents, international test scores (PISA, TOEFL iBT, EF EPI), national exam results (UN Indonesia and CSAT Korea), and structured questionnaires involving 800 students and 200 teachers from both countries. The results showed a significant difference in the integration of curriculum technology (χ² = 24.7; p < 0.001), where South Korea allocated 85% of curriculum content to digital platforms, while Indonesia only 35%. Teaching methods in Indonesia are still dominated by the grammar-translation approach (68% of teachers), while South Korea adopts task-based learning (89% of teachers) which is positively correlated with student motivation (r = 0.62; p < 0.01). South Korean students' learning outcomes are consistently superior, with an average EF EPI score of 611 compared to 492 in Indonesia (t = 8.34; p < 0.001), especially in speaking skills (∆ = 15.3 points). Regression analysis revealed that 45% of the variance in learning outcomes in South Korea was influenced by technology (β = 0.52; p < 0.001), while in Indonesia, teacher quality was the main predictor (β = 0.38; p < 0.05). These findings confirm that disparities in learning outcomes are not only due to curriculum differences, but also structural factors such as infrastructure gaps, teacher capacity, and access to technology. The research recommends increasing digital-based teacher training and equitable distribution of infrastructure in Indonesia, as well as reforming the hagwon system in South Korea to reduce social inequality. The implications of this study are evidence-based policy contributions for the development of inclusive and adaptive language education in the digital era.